Curtain Control Systems Development on Mesh Wireless Network of the Smart Home - Trio Adiono; Sinantya Feranti Anindya; Syifaul Fuada; Maulana Yusuf Fathany (Institute of Advanced Engineering and Science, 2018)
In this paper, a curtain controller for smart home is presented. The aim of this work is to develop an end device in smart home system that will support power conservation function indirectly, specifically a curtain open/close controller. To achieve this, the 28BYJ-48 stepper motor is used as actuator with the assistance of ULN2003A driver. The motor is controlled using STM32L100RCT6 microcontroller, which is chosen due to its low power consumption. The microcontroller controls the motor’s direction by using a pulse width modulation logic signals emitted from four GPIO pins, which works based on data transmitted from central host through ZigBee protocol on Mesh network. Meanwhile, from the user’s side, the control is done by using Android-based application, which is connected to central host through Bluetooth. Based on the testing conducted on a miniature curtain, the curtain can be controlled wirelessly through the Android application. Furthermore, the device consumes power 210.5 mW for idle condition and 1,586 mW for process condition. The amount of the consumed power makes it suitable for low-power operation and in alignment with the smart home system’s overall aim for power conservation in the wireless sensor network-based smart home system.